Patients and Their Families’ Perception on The Performance of Nurses with Certified Wound Care Competency - Bratajaya, Cicilia Nony Ayuningsih; Ernawati, Ernawati (Jurnal Keperawatan Soedirman, 2025)
Chronic wound care for patients with diabetes mellitus requires long and challenging treatment. Nurses’ skills and the right approach are certainly needed to enhance the healing process. In Indonesia, there was no study aimed at exploring wound care nurses’ skills. Therefore, this study aimed to explore patients’ experiences with chronic diabetic ulcers treated by wound care nurses. Specifically, to identify important skills of the nurses that would enhance the wound healing process. This qualitative phenomenological study involved seven participants with chronic diabetes mellitus ulcers who received wound care within the last six months which were recruited through purposive sampling. Data was obtained using semi-structured questions and analyzed using the Colaizzi approach. This study emerged with two themes: (1) The indispensable skills for wound healing; and (2) education as a complement to treatment. Hard skills are needed: wound care management, wound evaluation, and digital literacy. Soft skills: team skills, positive work ethics, and social skills; the nature of the disease, frequency of visits, nutrition, and treatment options were the information needed by study participants. In wound care, nurses need specific hard and soft skills. Studies on skills for wound care nurses still need to be carried out in various contexts.